Identifying factors associated with detection of sessile gastric polyps in patients with familial adenomatous polyposis - Mankaney, Gautam N.; Cruise, Michael; Sarvepalli, Shashank; Bhatt, Amit; Liska, David; Burke, Carol A. (Endoscopy International Open, 2022)
Background and study aims Gastric cancer (GC) is increasingly reported and a leading cause of death in patients with familial adenomatous polyposis (FAP). Identifying features in patients with FAP who harbor sessile gastric polyps, likely precursors to GC, may lead to alterations in endoscopic surveillance in those patients and allow endoscopic intervention to decrease the risk of GC. The aim of this study was to identify demographic and clinical factors in patients with FAP who harbor sessile gastric polyps.Patients and methods We retrospectively compared demographic, clinical, and endoscopic features in consecutive adult patients with FAP who presented for a surveillance endoscopy at a tertiary-care center with a FAP registry who harbor sessile gastric polyps to those without them. Sessile gastric polyps included pyloric gland adenomas, gastric adenomas, hyperplastic polyps, and fundic gland polyps with high-grade dysplasia. We also display the location of germline APC pathogenic variants in patients with and without sessile gastric polyps.Results Eighty patients with FAP were included. Their average age was 48 years and 70 % were male. Nineteen (24 %) had sessile gastric polyps. They were older (P < 0.03), more likely to have a family history of GC (P < 0.05), white mucosal patches in the proximal stomach (P < 0.001), and antral polyps (P < 0.026) compared to patients without a gastric neoplasm. No difference in Spigelman stage, extra-intestinal manifestations, or surgical history was note. 89 % of patients with a gastric neoplasm had an APC pathogenic variant 5’ to codon 1309.Conclusions Specific demographic, endoscopic, and genotypic features are associated with patients with FAP who harbor sessile gastric polyps. We recommend heightened awareness of these factors when performing endoscopic surveillance of the stomach with resection of gastric neoplasia when identified.